Fire safety model applying on workplaces of Fire and rescue departments in Kuala Lumpur city Malaysia - Askari, Arameh; Ishak, Mohd Bakri; Halimoon, Normala; Mohamad kashim, Mohamad Roslan; Shamzipour, R.; Omar, Dasimah (RS Publication, 2015)
Occupational health & safety (OSH) are conditions and factors that affect, or may affect the health and safety of employees or employees wile at work. Certified OHSM systems have become an important instrument for organization in their efforts to make a work environment healthy and safe (Gallagher et al., 2001; Underhill & Rimmer, 2001, Frick and Wren, 2000; Robson et al., 2007; Rocha, 2010).Therefore, here for having a safe workplace first most problematic hazard were determined in this study, then a safety model regarding to the issue were proposed. Result reported that fire explosion was a highest hazard in the fire and rescue department in Kuala Lumpur city that is why the propose model most consider on fire as a hazard.